2019
DOI: 10.1097/mat.0000000000000822
|View full text |Cite
|
Sign up to set email alerts
|

Novel Leukocyte Modulator Device Reduces the Inflammatory Response to Cardiopulmonary Bypass

Abstract: Leukocyte activation during cardiopulmonary bypass (CPB) promotes a systemic inflammatory response that contributes to organ injury and postoperative organ dysfunction. A leukocyte modulatory device (L-MOD) for use during (and after) CPB to limit leukocyte-mediated organ injury was tested in a preclinical model. Twenty-two pigs underwent 180 minutes of CPB and 5 hours postoperative observation. Pigs received no intervention (group 1, n = 9), 3 hours of therapy by incorporation of L-MOD into the CPB circuit (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…An inclusion criterion of intent to treat with SCD for at least 96 hours was included in the original clinical protocol due to prior clinical experience demonstrated that 72 to 96 hours of treatment was required to see clinical and laboratory improvement. For the CC group, all ICU patients from CRRTnet were identified with COVID-19 disease and selected after meeting all inclusion/exclusion criteria similar to the treated group ( 27 ). Only patients from the registry that began CRRT treatment during the study period were included into the CC group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An inclusion criterion of intent to treat with SCD for at least 96 hours was included in the original clinical protocol due to prior clinical experience demonstrated that 72 to 96 hours of treatment was required to see clinical and laboratory improvement. For the CC group, all ICU patients from CRRTnet were identified with COVID-19 disease and selected after meeting all inclusion/exclusion criteria similar to the treated group ( 27 ). Only patients from the registry that began CRRT treatment during the study period were included into the CC group.…”
Section: Methodsmentioning
confidence: 99%
“…These bound leukocytes are deactivated and returned back to the systemic circulation (20). This continuous cell processing activity results in measurable diminution of excessive inflammatory responses with improvement of solid organ dysfunction in a variety of preclinical and clinical studies, including sepsis, AKI, ischemia/ reperfusion injury, intracerebral hemorrhage, cardiopulmonary bypass, chronic kidney disease, and type 2 diabetes mellitus (21)(22)(23)(24)(25)(26)(27)(28). This approach was recently evaluated under expanded/emergency use in four ICU COVID-19 patients with cytokine storm and severe ARDS requiring ECMO, and the encouraging results in the first two cases treated were reported (29).…”
mentioning
confidence: 99%
“…Accordingly, the extracorporeal immunomodulation approach with SCD treatment warranted an evaluation first in a preclinical model of systolic CHF prior to translation into the clinical setting. In preclinical models, SCD therapy has shown efficacy in acute multiorgan injury in severe sepsis, cardiopulmonary bypass, intracerebral hemorrhage (ICH), and ischemia/reperfusion injury (IRI) (10)(11)(12)(13)17). This device has been tested in 6 clinical studies in ICU patients with acute kidney injury and multiorgan dysfunction requiring dialysis and COVID-19 patients with adult respiratory distress syndrome (ARDS) with improved clinical outcomes and no device-related serious adverse events (14)(15)(16)18,19,23).…”
Section: Discussionmentioning
confidence: 99%
“…This continuous autologous cell processing activity results in measurable diminution of excessive inflammatory responses with improvement of solid organ dysfunction in a variety of preclinical and clinical studies, including sepsis, acute kidney injury, ischemia/reperfusion injury, intracerebral hemorrhage, cardiopulmonary bypass, adult respiratory distress syndrome, chronic kidney disease, and type 2 diabetes mellitus (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…The relationship between surgical intervention and cardiopulmonary bypass has been widely postulated [ 17 , 18 , 19 , 20 ]. Despite surgical challenges, the off-pump technique (off-pump coronary artery bypass surgery, OPCAB) can be performed safely by experienced surgeons and may rule out the risk of inflammatory activation that is secondary to CPB application [ 21 ].…”
Section: Introductionmentioning
confidence: 99%